Growth and Graduation of Vannamei Shell Life (Litopenaeus Vannamei) with Feeding Tray (ANCO) System in AV 8 Lim Shrimp Organization (LSO) in Sumbawa District - Syamsul Bahri; Dwi Mardhia; Osi Saputra (Universitas Mataram, 2020)
Vannamei shrimp species look for lunch and dinner. These properties need to be known related to the amount of feed and frequency of feeding to be given. Because wasted feed is expensive and can reduce water quality, optimizing feeding practices is an important issue in shrimp culture management. The use of some ANCOs is intended to monitor feed consumption and estimate feed adjustments. So it is necessary to conduct research on the growth and graduation of vannamei shrimp (Litopenaeus Vannamei) with the feeding tray (ANCO) system in Av 8 Lim Shrimp Organization (LSO) in Sumbawa Regency. The method used in this research is descriptive method, namely research based on reality and the facts of the situation as it is. The results showed that the amount of feed every week or sampling is always different, this is because the amount of feed adjusted to the addition of shrimp growth every sampling. Addition and reduction of feeding is adjusted to the results of checking feed consumption on ANCO, adding the amount of feeding is done if when checking ANCO there is no feed left. Reduction in the number of gifts is done if when checking ANCO still left feed. In the 8th sampling the amount of feed decreased to 38 kg, this was due to the first partial harvest. In the 10th sampling is the lowest amount of feeding which is 30 kg, this is due to the second partial harvest, but in the 11th sampling the number of feeding again increased so that the shrimp could grow to its maximum potential during panentotal.